Insecticidal Activity of Some Chemicals of Mosquitoes Culex pipiens molestus Forskal (Baghdad Science Journal, 2021)
The chemicals materials were used to study the effect of citric acid, detergents, sodium carbonate, sodium bicarbonate on the vitality of the third stage of mosquito Culex pipiens molestus. The highest larvicidal efficacy was established from citric acid solution followed by detergents solution, sodium carbonate, sodium bicarbonate with (LC50) values 2096, 2715, 13930, 13960 ppm respectively. The concentration of 1000 ppm of citric acid showed a fatal effect on the third stage larvae of mosquitoes which gave a mortality percent of 100% on the second day of the treatment. It was followed by the concentrations of 750 ppm and 500 ppm respectively which caused the death of all larvae on the fifth and sixth days respectively. On the other hand, the concentration of 1500 ppm for the detergents killed 100% of the larvae on the third day of treatment. Then, it was followed by the concentration of 1000 ppm, leading to the destruction of all the larvae on the fifth day of the exposure. As for the use of sodium carbonate, the mortality percentage reached to 100% at a concentration of 8000 ppm on the third day of treatment followed by the concentration of 6000 ppm, which led to a 100% killing rate on the sixth day of treatment. While the less impact of studied chemicals was sodium bicarbonate, the 8000 ppm concentration of which caused 84.21% mortality rate of larvae on the fourth day of treatment.